2016
DOI: 10.1016/j.aquatox.2016.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to phenanthrene and depuration: Changes on gene transcription, enzymatic activity and lipid peroxidation in gill of scallops Nodipecten nodosus

Abstract: Understanding the mechanism of phenanthrene (PHE) biotransformation and related cellular responses in bivalves can be an important tool to elucidate the risks of polycyclic aromatic hydrocarbons (PAHs) to aquatic organisms. In the present study it was analyzed the transcriptional levels of 13 biotransformation genes related to cytochrome P450 (CYP), glutathione S-transferase (GST), sulfotransferase (SULT), flavin-containing monooxygenase and fatty acid-binding proteins by qPCR in gill of scallops Nodipecten no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(7 citation statements)
references
References 75 publications
(92 reference statements)
1
6
0
Order By: Relevance
“…However, no increase was seen in the expressions of Gpx1 and Cat after BaP exposure. The absence of the up-regulation of these two antioxidant enzymes was also found in studies done with scallops of Chlamys farreri [50] , scallops N. nodosus [51] , and roach (Rutilus rutilus) [52] . It was demonstrated in cultured mouse embryos that SODs can significantly reduce the incidence of NTDs induced by BaP and ethanol [30] , [53] .…”
Section: Discussionsupporting
confidence: 55%
“…However, no increase was seen in the expressions of Gpx1 and Cat after BaP exposure. The absence of the up-regulation of these two antioxidant enzymes was also found in studies done with scallops of Chlamys farreri [50] , scallops N. nodosus [51] , and roach (Rutilus rutilus) [52] . It was demonstrated in cultured mouse embryos that SODs can significantly reduce the incidence of NTDs induced by BaP and ethanol [30] , [53] .…”
Section: Discussionsupporting
confidence: 55%
“…This result demonstrated that the antioxidant system of C. auratus may fail to scavenge overproduced ROS by co-exposure to Cu 2+ and Fluo. Owing to the wide surface area in contact with water, gills are an important uptake route of organisms for waterborne pollutants [42]. Among metal ligands, induced MTs are involved in non-enzymatic homeostasis and a detoxifi cation mechanism of fi sh against metal exposure.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…85,86 However, numerous studies have demonstrated that there are other signicant factors affecting the process of PAH bioaccumulation, including environmental characterization, the number of PAH rings, and the biometric characteristics and detoxication metabolism of organisms. [87][88][89] The bioaccumulation manifested a different PAH composition to the environment, and due to the specic uptake patterns, some sources may have higher importance to the biota. Previous research has predominantly assessed pollution risks based on the concentration of pollutants, overlooking their sources that also contributed to the overall risk.…”
Section: Source Apportionment Of Pahs In Seawater Sediment and Organismsmentioning
confidence: 99%